Compost stability and maturity evaluation — a literature review. Issue 5 (1st November 2013) - Wichuk, Kristine M.; McCartney, Daryl
Abstract : Finished compost should be both stable (resistant to decomposition) and mature (ready for a particular end-use) so that it can safely be packaged and transported, and not cause adverse effects during its end use. A variety of methods for evaluating stability and maturity are available; this paper contains a review of the effectiveness of a number of the most commonly used tests, to determine the most reliable approach(es). In the literature reviewed, it was generally agreed that a single, stand-alone test for both compost stability and maturity does not yet exist; therefore, it is best to use a combination of tests. However, there is disagreement in the literature as to what the best combination for evaluation should be, and guidelines and regulations around the world employ a variety of approaches.